Makna Motivasi dalam Video Klip Lagu “Teramini Ghea Indrawari” (Analisis Semiotika Jhon Fiske) - Syarafi Dwi Mansuri; Iin Soraya; Sari Ekowati (CV Edujavare Publishing, 2024)
With Gen Z's higher level of awareness of mental health, many of them are trying to provide motivation to themselves and others, especially those in the same generation as them. There are many motivations for what they do, one of which is by listening to songs or watching video clips that relate to them. In this era, apart from listening to songs or watching MVs, many of them are creating songs about mental health. This can be proven by the many motivational songs related to mental health on social media. The aim of this research is to find out the meaning of motivation in Ghea Indrawari's song